Impact resistance performance and comparative analysis of CFRP and steel strand anchors - Xin Fan; Ruixin Jia; Yize Zuo; Weiwei Liu; Yue Liu; Shuai Guan; Md Abdur Rakib; T. Tafsirojjaman (Results in Engineering)
In mountain road construction, strand anchors face rapid axial impacts from blasting slope excavations, necessitating high impact resistance for structural stability and durability. CFRP (Carbon Fiber Reinforced Polymer) strand anchors have more complex impact damage mechanisms than metal ones, influenced by various factors. In this study, impact resistance tests were conducted on 15.2 mm diameter CFRP and steel strand anchors. The results indicate the impact resistance of CFRP is approximately 15 % of that of steel strand anchors with the same diameter. The elongation caused by the impact is only 14 % of that under static load. A predictive formula for the maximum impact force of CFRP strand anchors under impact was developed, with experimental validation demonstrating an error margin of less than 5 % between theoretical and measured values.